Superior suspensory complex of the shoulder reconstruction for acute and chronic acromioclavicular joint dislocations: the Queensland Unit for Advanced Shoulder Research 3-tunnel technique - Helen Ingoe, MBBS, FRCS Eng, MD, MSc, PGCert; Jashint Maharaj, MBBS, MPHTM, FRSPH; Nagmani Singh, MBBS, MS; Kathir Azhagan Stalin, MBBS, MS, MRCS, DNB; Kristine Italia, MD, FPOA; Roberto Pareyon, MD; Mohammad N. Jomaa, MD; Kenneth Cutbush, MBBS, FRACS, FAOrthA; Ashish Gupta, MBBS, MSc, FRACS (JSES International)
Background: Management of acromioclavicular joint (ACJ) injuries have wide variety of classification systems, surgical indications and operative techniques. Our study describes the Queensland Unit for Advanced Shoulder Research (QUASR) 3-Tunnel Technique with Ligament Augmentation and Reconstruction System (LARS; Surgical Implants and Devices, Arc sur Tille, France) artificial ligament to reconstruct the superior shoulder suspensory complex in acute, chronic, and revision ACJ dislocations and lateral clavicle fractures. Methods: Our prospective cohort series of patients undergoing the QUASR 3-Tunnel Technique using LARS artificial ligament. This technique reconstructs the superior shoulder suspensory complex using 2 4-mm clavicle tunnels, 1 acromion tunnel, and is arthroscopically assisted to pass the artificial ligament under the coracoid. The ligament is secured with braided composite sutures and no interference screw is used. Preoperative and postoperative functional outcome scores were compared in patients with minimum 12-months follow-up. Results: Of 26 patients in this series, 7 (27%) were operated within 4 weeks of injury, 2 (8%) were revision cases, and 6 (23%) were lateral clavicle fractures. Mean time to surgery was 14 weeks (2-650). Mean postoperative scores with associated 95% confidence interval were Specific Acromioclavicular Score 87.38 (confidence interval 75.38-99.37), American Shoulder and Elbow Surgeons score 94.60 (87.85-101.35), Constant 79.47 (71.87-87.07), simple shoulder test 85.44 (72.34-98.54) and visual analog score 0.50 (−0.15 to 1.15). There were 2 infections and 1 atraumatic loss of reduction; however, there were no tunnel fractures. Conclusion: The QUASR 3-Tunnel Technique with LARS artificial ligament is a safe and efficient technique for both acute and chronic ACJ reconstruction, lateral clavicle fractures with coracoclavicular ligament disruption and complex revision cases with favorable outcomes at the mid-term follow-up.